2016
DOI: 10.17222/mit.2014.192
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the number of forward time steps for the sequential Beck approach used for solving inverse heat-conduction problems

Abstract: Direct heat-conduction problems are those whose boundary conditions, initial state and material properties are known and the entire temperature field in a model can be computed. In contrast, an inverse problem is defined as the determination of the unknown causes based on the observation of their effects. The inverse heat-conduction method is often used for problems where the boundary conditions cannot be measured directly but are computed from the recorded temperature history inside the model. A very effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The measured temperatures are used as input into the inverse heat conduction problem IHCP that gives the HTC, the surface temperature, and the heat flux in thermocouple positions in dependency on time, see Figure 4 . More about the IHCP used can be found in the study by Komínek et al [ 21 ]…”
Section: Methodsmentioning
confidence: 99%
“…The measured temperatures are used as input into the inverse heat conduction problem IHCP that gives the HTC, the surface temperature, and the heat flux in thermocouple positions in dependency on time, see Figure 4 . More about the IHCP used can be found in the study by Komínek et al [ 21 ]…”
Section: Methodsmentioning
confidence: 99%
“…The experimental data (temperatures measured) are used as input into the inverse heat conduction problem (IHCP) that gives HTC, surface temperature and heat flux over time. More about the IHCP used in this study can be found in [16,17] and the general principles of IHCP are in [18]. The use of an inverse task is necessary because the conclusions can be drawn only from surface temperatures, not from temperatures measured at a depth of 2 mm.…”
Section: Heat Transfer Coefficient and Leidenfrost Temperature Measurementmentioning
confidence: 99%
“…Heat transfer coefficient dependence on the position and surface temperature are obtained from these tests using inverse task (Figure 5). Detail information about inverse task could be found in [11][12][13][14][15]. Cooling intensity and homogeneity is evaluated by comparison of obtained heat transfer coefficient dependences on the surface temperature for selected position interval.…”
Section: Figurementioning
confidence: 99%